Stig Sjödin och minnets politik - Nilsson, Magnus (Scandinavistica Vilnensis, 2023)
The aim of this article is to analyse the attitudes to history and memory expressed in the working-class poetry of Stig Sjödin (1917–1993) – both in Sotfratgment (Fragments of Soot) from 1949, which marked his breakthrough as a poet, and in the poetry he wrote for the labour movement (mainly poems published in tradeunion membership magazines or read at meetings and congresses) – and to discuss how he and his poetry are today viewed as reminders of political ideals and experiences threatened by oblivion. There are certain differences between how memory and remembering is treated in Sotfragment and in Sjödin’s labour-movement poetry respectively. In Sotfragment, focus is more often on individual memories and existential problems, whereas in the labour-movement poetry, Sjödin is sometimes more explicitly political and writes about collective memories from a proletarian perspective. These differences are conditioned by differences between the spheres to which the poems belong: that of literature and that of the labour movement. In connection with the rise of left-wing radicalism in Sweden during the 1960s and 1970s, Sjödin argued that older working-class literature contained important political experiences and perspectives. This is also how his works are sometimes viewed today, both by working-class writers and by political commentators. Thereby, it is emphasized that literature is not a passive medium for the preservation of memories, but that it can also transform them and make them politically relevant.